Measuring relative utilization of aerobic glycolysis in breast cancer cells by positional isotopic discrimination. Issue 18 (1st September 2016) - Yang, Da‐Qing; Freund, Dana M.; Harris, Benjamin R. E.; Wang, Defeng; Cleary, Margot P.; Hegeman, Adrian D.
Abstract : The ability of cancer cells to produce lactate through aerobic glycolysis is a hallmark of cancer. In this study, we established a positional isotopic labeling and LC‐MS‐based method that can specifically measure the conversion of glucose to lactate in glycolysis. We show that the rate of aerobic glycolysis is closely correlated with glucose uptake and lactate production in breast cancer cells. We also found that the production of [3‐ 13 C]lactate is significantly elevated in metastatic breast cancer cells and in early stage metastatic mammary tumors in mice. Our findings may enable the development of a biomarker for the diagnosis of aggressive breast cancer. Abstract :